The Effects of Comprehensive Reading Strategy Instruction on Elementary Students’ Reading Comprehension: A Quasi-Experimental Study - Surismiati Surismiati; Gunawan Gunawan; Ayu Wulandari; Mustofa Mustofa; Danto Danto; Kurnia Saputri; Jeni Amiriski (AL-ISHLAH: Jurnal Pendidikan, 2026)
Reading comprehension is a fundamental literacy skill that significantly influences the academic achievement of elementary school students. Despite its importance, classroom reading instruction frequently emphasizes surface-level activities and lacks explicit, integrated teaching of reading strategies. The present study investigates the impact of comprehensive reading strategies on the reading comprehension ability of elementary school students. A quasi-experimental design was employed, utilizing a pretest–posttest control group model. Data analysis was conducted using an independent t-test on posttest scores. The sample comprised 60 grade V students from SD Muhammadiyah 16 Palembang, divided equally into experimental (n = 30) and control groups (n = 30). The experimental group received integrated, strategy-based reading instruction encompassing pre-reading, while-reading, and post-reading stages, whereas the control group received conventional reading instruction. Reading comprehension was assessed using a test measuring four aspects: literal, inferential, critical, and creative comprehension. Data were analyzed with an independent sample t-test after confirming normality and homogeneity of variance. Results indicated that the experimental group achieved a higher posttest mean score (M = 82.30) compared to the control group (M = 71.25). This difference was statistically significant, t(58) = 4.87, p .001, with a large effect size (Cohen's d ≈ 1.26). These findings indicate that comprehensive reading strategies are effective in enhancing elementary students’ reading comprehension. Successful implementation of these strategies requires teacher training and systematic integration into the elementary reading curriculum. Limitations of the study include non-randomized group assignments, restriction to a single school, and a relatively short intervention period.